Editorial - Cantisani, Vito (Ultrasound International Open, 2020)
Dear Colleagues,It is a pleasure to introduce the present issue of Ultrasound International Open.It contains an updated overview of how handling ultrasound systems, fundamental adjustments, and their optimization in B-mode ultrasound provided by Dr. Zander and colleagues.